Resolusi Guru PAI Terhadap Tantangan Pembelajaran Pendidikan Agama Islam di Era Revolusi Industri 4.0 (Studi Kasus Pada SMP Negeri 1 Rasau Jaya Kubu Raya) - Muhammad Basarrudin (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2025)
The teacher's resolution is the planning or movement of change that the teacher makes in the learning process in the classroom so that learning can go well. The aim of this study is to find out the problems faced by teachers of Islamic religious education when they study PAI in the era of the Industrial Revolution 4.0, as well as the factors that caused obstacles or challenges in PAI learning in the age of the industrial revolution 4.0. Field research or case studies is a type of research that uses techniques and data processing such as observations, interviews, and documentation. Data validity testing techniques include credibility, transferability, dependability, and confirmability. Data analysis techniques also include data collection, data reduction, and data appearance. (data display). The results of this study show that the change of times can have a considerable impact on the world of education, including the learning of Islamic education. At 1 Rasau Jaya Kubu Raya State High School, PAI teacher has completed the challenge of learning Islamic religious education in the era of the industrial revolution 4.0, so it can be concluded that the resolution is running well and well received by students.